Aqueous extract of Cyperus rotundus on the rooting of Prunus persica cv. ‘Chimarrita’ cuttings (Revista de Ciências Agroveterinárias, 2017)
Although growth regulators of the auxin group are normally used to induce rooting of cuttings, in recent years, research has been of interest to obtain alternative methods for the induction of rhizogenesis in cuttings of plants with difficult vegetative propagation, such as Peach tree cv. ‘Chimarrita’. This makes the Cyperus rotundus L. a large-scale plant found in much of the world, an alternative for the induction of rooting in cuttings, because it has phenolic compounds that have a synergistic effect with the endogenous auxin. The objective of this study was to evaluate the rooting capacity of hardwood peach cuttings with the application of different concentrations of aqueous extract of C. rotundus L. in comparison with the application of the plant growth regulator indole-3-acetic acid. The treatments consisted of different concentrations of the aqueous extracts of roots and shoots of C. rotundus L. and the growth regulator indole-3-acetic acid. The percentage of live cuttings, rooted cuttings, callus, and the length of roots and dry matter of the root system were evaluated. The aqueous extract of shoot and root system of C. rotundus L. does not promote the rooting of hardwood peach cuttings cv. ‘Chimarrita’ within 90 days. The 500 mg L-1 concentration of indole-3-acetic acid promotes greater rooting of the hardwood peach cuttings.
Keywords: cutting; nutgrass; peach; vegetative propagation; indole-3-acetic acid.